Meningkatkan Keterampilan Konseling dengan Mind Skills - ahmad baikuni (Ulumuna: Jurnal Studi Keilsman, 2015)
Counseling service is a service to help counselee in obtaining their understanding to be used in their life time. So they can determine the better choice that is useful and suitable with their environment condition. Counselee will obtain a good skill when the counselor is not only able to use the technique and communication of counseling but also how to arrange their mind which is called as mind skill that can be trained with experiential learning. This article tries giving an argument and theoretical review about the importance of mind skill in a counseling because empirical researches find out some of counselors that are not able to give counseling service comprehensively, the fact counselor tend to fall in their selfishness, then they are dominated by their negative self-talk and they tend to act more experienced and then transfer their experience to the counselee